Mechanical behaviour of organic matrix composites : effect of thermo-oxidative ageing /: effect of thermo-oxidative ageing. (2018) - Gigliotti, Marco; Lafarie-Frenot, Marie-Christine; Grandidier, Jean-Claude; Miunervino, Matteo
No abstract available